News Framing of the Protest Against the Elimination of Teacher Allowances in Samarinda City by Kaltim Newspaper - Romadhani, Tri; Nurliah, Nurliah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This research aims to analyze how Koran Kaltim Daily Newspaper framed the news related to the protest of the elimination of allowances carried out by teachers under the auspices of the Samarinda City government. This is done to know and understand the meaning contained in the news and how Koran Kaltim framed the polemics that occurred in the community. The focus of this research refers to the news framing theory by Scheufele which classifies framing techniques into 4 techniques namely defining problems, diagnosing causes, making judgments, suggesting remedies.This research uses a descriptive qualitative approach with the framing model analysis technique by Zhondang Pan & Gerald M. Kosicki, which divides framing into 4 major structures namely syntactic, script, thematic, and rhetorical structures. Data were collected in the form of news texts containing the adjustment of teacher allowances in Samarinda City by Koran Kaltim as many as 5 news articles published on September 30, 1, 4, 12, and October 18, 2022. The results showed that Kaltim Newspaper tended to favor the government of Samarinda City, this can be seen from the provision of more news portions to the government. The teachers are only given space as an opening that determines the direction of the conflict, the rest of the teachers are described as only emphasizing and following the statements issued by the Samrinda City government. The framing of conflict news is packaged with subtle language and does not tend to show criticism of the policies taken, as seen from the use of idioms that have multiple meanings so that they do not clearly show criticism of the government.